Water Management for Kerian Irrigation Scheme Using Geographical Information System - Kamal, Md. Rowshon (2000)
A GIS-based model was developed to integrate the vast amounts of spatially distributed information of the Kerian Irrigation Scheme. The scheme has a command area of 24,000 ha, comprising eight compartments which is further subdivided into 28 blocks. The model requires the input of spatial and temporal information from various fields to compute irrigation deliveries for the upcoming period. It also runs periodic and seasonal monitoring and evaluation programs to improve water management of the scheme. The system permits display of information in the form of maps for easy visualization. The software Map Info Professional 4.5 was used to demonstrate the concepts and MapBasic Professional 4.5 programming language for the development of the user-interface tool. The scheduling program computes irrigation deliveries based on spatial and temporal demand of the paddy field by each compartment, block and Secondary Canal. The monitoring program gives information by compartment and by block at the end of each period on uniformity of water distribution to the field as well quantity to be delivered for the next period. The computed discharges were used to monitor the performance of irrigation delivery at the end of each period. Relative Water Supply (RWS), Water Use Efficiency (WUE), Cumulative Relative Water Supply (CRWS), Water Productivity Index (WPI) and Cropping Intensity (CI) have been used for monitoring and evaluation of the irrigation system performances. Hydro-climatological parameters like Evapotranspiration (ET), Effective Rainfall (ER), Irrigation Depth (IR) and Drainage Requirement (DR) also were computed. The post-season analysis provides weekly distribution of hydro-climatological parameters, irrigation delivery and performance by block. On a weekly basis, RWS and WUE were found to range from 1.01 to 2.24 and 45% to 99% respectively in the main season and 1.01 to 1.87 and 53.6% to 96.2% in the off season. The average values of RWS and WUE were found to be 1.53 and 68.15% in the main season and 1.33 and 78.5% in the off season respectively. The average values of WPI were also found to be 0.1267 and 0.2171 kg/m3 in the main season and off season respectively. The color-coded thematic maps were produced for the monitoring of seasonal yields and cropping intensity by block and compartment of the scheme. The user-interface technique for the irrigation system promises to provide comprehensive results along with new data sets and improve the decision-making processes in the operation and management of the scheme. The computed results are rapidly displayed allowing the manager to view maps, tables and graphs in a more comprehensive form, allowing time to make appropriate decision as the season progresses. This technique was found to be for improving the irrigation system management along with the actual feedback of the field information.